Design and Development of a Web-Based Company Profile for PELNI Logistics Using the Waterfall Model - Darussalam, Muhammad (Jurnal Multidisiplin Sahombu, 2025)
The rapid evolution of information technology has transformed the way companies communicate and present their profiles to the public. This study focuses on the design and development of a web-based company profile for PELNI Logistics to support an integrated information system that enhances accessibility, efficiency, and corporate image. The development process applies the Waterfall model, covering requirement analysis, system design, implementation, testing, and maintenance. The system is built using a combination of web programming languages and a relational database, supported by data obtained through observation, interviews, and documentation. The resulting platform provides comprehensive company information, including corporate background, governance, services, portfolio, news updates, procurement, and career opportunities. Testing demonstrates that the platform functions effectively, ensuring user-friendly navigation, accurate information delivery, and responsive design across various devices. The implementation of this system strengthens the company’s digital presence, supports transparent communication with stakeholders, and serves as a practical reference for other logistics companies seeking digital transformation.